2017
DOI: 10.1177/0958928717709174
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in the realized retirement age: Europe in times of pension reform and economic crisis

Abstract: Many recent policy reforms aimed to delay retirement. Such a delay seems important because population ageing makes it a necessity for financially sound pension schemes and a sufficiently large workforce. However, pension reforms do not only affect when people retire, they likewise affect what influences the realized retirement age. Moreover, the 2008 economic crisis restructured labour markets, thereby affecting retirement. This article investigates recent shifts in the realized retirement age and influences o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…Moreover, it provides models for estimating what newly emerging life-course patterns could be. Most notably, recent studies pointed to increasing unemployment due to the 2008 recession and the on-going social change in Eastern Europe [53, 65, 66]. In the wake of the 2008 crisis, unemployment rates increased especially among youths, who could not establish themselves in the labor market, and among older individuals, who sometimes responded with early retirement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it provides models for estimating what newly emerging life-course patterns could be. Most notably, recent studies pointed to increasing unemployment due to the 2008 recession and the on-going social change in Eastern Europe [53, 65, 66]. In the wake of the 2008 crisis, unemployment rates increased especially among youths, who could not establish themselves in the labor market, and among older individuals, who sometimes responded with early retirement.…”
Section: Discussionmentioning
confidence: 99%
“…Such life-course patterns are most likely to emerge in Southern and Eastern Europe over the coming years. The reasons are that especially Southern European countries suffered during the 2008 crisis [53], and that Eastern European countries are still transforming as they transition into market economies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…"However, pension reforms not only affect the way people retire, but also their retirement age. Moreover, the 2008 economic crisis has rebuilt labor markets, which has had an impact on retirement" (Komp, 2017).…”
Section: According To the Organization For Economicmentioning
confidence: 99%
“…Young adults were disproportionately negatively affected through rising rates of unemployment and the growth of precarious forms of work (Aassve et al, 2013;Bell and Blanchflower 2011;Connidis 2014;Crosnoe 2014;Mortimer 2014;Whelan et al 2017), leading to greater difficulties attaining independence. Older Europeans experienced significant losses of net wealth during the crisis, giving rise to financial distress amongst those with low incomes (Cavasso and Weber 2013) and to delayed retirement in some countries (Komp 2017;Meschi et al 2013). A number of studies demonstrated that adults at mid-life experienced comparatively high levels of stress linked to their intergenerational responsibilities (Connidis 2014;McDaniel et al 2013), and where there were high levels of indebtedness (Watson et al 2016).…”
Section: Introductionmentioning
confidence: 99%